Myocyte Culture with Decellularized Skeletal Muscle Sheet with Observable Interaction with the Extracellular Matrix - Satoshi Nakada; Yuri Yamashita; Seiya Akiba; Takeru Shima; Eri Arikawa-Hirasawa (Bioengineering, 2022)
In skeletal muscles, muscle fibers are highly organized and bundled within the basement membrane. Several microfabricated substrate models have failed to mimic the macrostructure of native muscle, including various extracellular matrix (ECM) proteins. Therefore, we developed and evaluated a system using decellularized muscle tissue and mouse myoblasts C2C12 to analyze the interaction between native ECM and myocytes. Chicken skeletal muscle was sliced into sheets and decellularized to prepare decellularized skeletal muscle sheets (DSMS). C2C12 was then seeded and differentiated on DSMS. Immunostaining for ECM molecules was performed to examine the relationship between myoblast adhesion status, myotube orientation, and collagen IV orientation. Myotube survival in long-term culture was confirmed by calcein staining. C2C12 myoblasts adhered to scaffolds in DSMS and developed adhesion plaques and filopodia. Furthermore, C2C12 myotubes showed orientation along the ECM orientation within DSMS. Compared to plastic dishes, detachment was less likely to occur on DSMS, and long-term incubation was possible. This culture technique reproduces a cell culture environment reflecting the properties of living skeletal muscle, thereby allowing studies on the interaction between the ECM and myocytes.